Comparison of registered and survey-based modes of HIV transmission in 2021–2023: Cross-sectional study in the Kyrgyz Republic - Kostyantyn Dumchev; Anastassiya Stepanovich-Falke; Nikolay Lunchenkov; Anna Rohde; Anastasiya Danshyna; Aibek Bekbolotov; Aigul Solpueva; Aidana Kenzhekarieva; Aida Karagulova; Elmira Narmatova; Olga Varetska; Stela Bivol; et al. (PLoS ONE, 2025)
Background Accurate identification of the mode of transmission (MoT) of HIV is critical for effective prevention. However, stigma associated with behaviors such as injecting drug use (IDU) and sex between men (MSM) can lead to misclassification of MoT data. This study replicates the methodology used in Ukraine to assess MoT misclassification and trends in Kyrgyzstan, with the aim of informing evidence-based epidemic control strategies. Methods A cross-sectional survey was conducted among patients diagnosed with HIV in the six largest administrative units of Kyrgyzstan during the first three quarters of 2021–2023. The survey assessed pre-seroconversion HIV risk factors using self-administered, interviewer-assisted questionnaires, and HCV testing. The McNemar test compared registered and survey-based MoT, while logistic regression analyzed MoT trends over time. Results A total of 1,962 new HIV diagnoses were registered in the study period, of them 480 individuals completed the survey. The proportion of cases attributable to IDU and MSM was higher in the survey than in the registration system (8.1% vs. 4.2%, p = 0.001 for IDU; 14.2% vs. 11.7% p = 0.12, for MSM), whereas heterosexual MoT was lower (76.0% vs. 80.2%, p = 0.038). Selling sex was reported by 2.9%, and in combination with IDU and MSM, 23.5% of participants could be categorized into one of the three key populations. An additional 18.1% belonged to bridge populations. There was a 23% increase in the absolute number of registered patients in the corresponding periods over three years, but the MoT distribution did not change. Conclusion We found significant misclassification in IDU and heterosexual MoT, but not in MSM, possibly due to suboptimal survey sensitivity amid the increased stigmatization of the LGBTQI+ community. At least 41% of newly registered cases in Kyrgyzstan occurred in key and bridge populations, highlighting the need for intensified prevention efforts in these groups. Understanding the mode of transmission (MoT) of HIV among newly diagnosed people living with HIV (PLHIV) is critical for monitoring the epidemic and targeting prevention efforts [1]. Assessment of MoT often relies on self-reporting of HIV risk behaviors by patients, which can be inaccurate, especially when associated with stigma or criminalization [2–4]. This is particularly true for injecting drug use (IDU), which is criminalized and stigmatized in many countries [5,6]. Stigma and discrimination against men who have sex with men (MSM) exist in many parts of the world [7,8], leading to underreporting of this behavior even in settings with increasing acceptance [9]. Misclassification of MoT in HIV surveillance systems may be exacerbated by the lack of standardized tools to collect sensitive information or by clinicians’ reluctance to inquire about behaviors that have no impact on patient management.